Anesthesia Management in Morbidly Obese Patient Undergoing Neurosurgical Procedure: A Case Report - Charles; Cynthia Dewi Sinardja (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Anesthesia management in morbidly obese patients undergoing any neurosurgical procedure is particularly challenging. This case report aims to further discuss the importances and concerns regarding the anesthesia management of decompression craniectomy in morbidly obese patients. Case presentation: A 46-years-old male patient was diagnosed with intracerebral hemorrhage on regio left external capsule due to hypertensive emergency suspected from Middle Cerebral Artery (MCA) aneurysma rupture. Decompression craniectomy with clot evacuation was planned. This patient has morbid obesity. Prediction of difficult intubation and mask ventilation can be assessed using LEMONS, MOANS, Mallampati score and STOP-Bang Questionnaire. The dosage of anesthetic agents used in these patients had been adjusted according to current recommendations. Intraoperatively, patient’s hemodynamic was successfully maintained stable. Postoperatively, patient was closely monitored in the intensive care unit. Conclusion: It is imperative to acquire adequate knowledge on choosing the effective anesthetic management during the preoperative, intraoperative, and postoperative periods to achieve good outcome in morbidly obese patient undergoing neurosurgical procedures.